Formulating Strategy Through Boston Consulting Group Matrix In The Tourism Industry - Aprilia, Sonia; Lionora, Clarisa Alfa; Aprilistyan, Syifa Freza (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2023)
The existence of the Covid-19 virus impacts daily activities carried out by humans, not only killing the human body but also economic growth throughout the region. One of the sectors affected by the Covid-19 pandemic is tourism, for example, in the Magelang City area, precisely in Kyai Langgeng Park. Kyai Langgeng Park has experienced a decline since the arrival of the Covid-19 virus, and it has impacted the surrounding economy and company income. This paper aims to determine market share and industry growth that needs to be developed through the BCG matrix analysis tool. This research uses quantitative methods from the results of BCG matrix analysis. It takes secondary data from the number of tourists according to tourism objects in Magelang City in 2016-2020, which are sourced from the Youth, Sports, and Tourism Office of Magelang City. The results of this study indicate that Kyai Langgeng Park is in the cash cow quadrant due to sales growth of -71.26% and a relative market share of 0.534. The results of this study are expected to help Taman Kyai Langgeng develop and improve its business strategy to survive in the era of increasingly fierce industrial competition.